Altered Amplitude of Low-Frequency Fluctuations and Functional Connectivity in Excessive Daytime Sleepiness in Parkinson Disease - Wang, Xixi; Wang, Min; Yuan, Yongsheng; Li, Junyi; Shen, Yuting; Zhang, Kezhong (Frontiers in Neuroscience, 2020)
Object: Excessive daytime sleepiness (EDS) is common in Parkinson disease (PD), but the neural basis of EDS in PD is unclear. We aim to analyze the neural activity changes in PD-related EDS. Methods: In the present study, 38 PD patients and 19 healthy controls underwent clinical assessments and resting state functional magnetic resonance imaging (MRI) at 3T. Patients were further classified into PD patients with EDS (n=17) and PD patients without EDS (n=21), according to the Epworth Sleepiness Scale (ESS) cutoff score with greater than 10 or less than 3. We evaluated all patients using PD-related motor and non-motor clinical scales. An analysis of covariance and post hoc two-sample t-tests were performed to examine between-groups differences of the amplitude of low-frequency fluctuations (ALFF) and functional connectivity (FC). Results: We found that, all PD-EDS subjects in our study were male. Compared with the control subjects, PD patients with EDS had decreased ALFF in the Pons and increased ALFF in the Frontal_Mid_Orb_L (p < 0.01, corrected). Moreover, PD patients with EDS showed decreased ALFF in the left posterior cingulate cortex (PCC) relative to PD without EDS, which was negatively correlated with the ESS score (p < 0.001). After that, the FC analysis with the left PCC region of interest showed reduced FC of the right PCC and right precuneus in PD with EDS compared with PD without EDS (p < 0.01, corrected). Conclusion: We hypothesized the wake-promoting pathways and the default mode network dysfunction underlying the EDS in male PD patients.